Neurally Released GABA Acts via GABAC Receptors to Modulate Ca2+ Transients Evoked by Trains of Synaptic Inputs, but Not Responses Evoked by Single Stimuli, in Myenteric Neurons of Mouse Ileum - Koussoulas, Katerina; Swaminathan, Mathusi; Fung, Candice; Bornstein, Joel C.; Foong, Jaime P. P. (Frontiers in Physiology, 2018)
γ-Aminobutyric Acid (GABA) and its receptors, GABAA,B,C, are expressed in several locations along the gastrointestinal tract. Nevertheless, a role for GABA in enteric synaptic transmission remains elusive. In this study, we characterized the expression and function of GABA in the myenteric plexus of the mouse ileum. About 8% of all myenteric neurons were found to be GABA-immunoreactive (GABA+) including some Calretinin+ and some neuronal nitric oxide synthase (nNOS+) neurons. We used Wnt1-Cre;R26R-GCaMP3 mice, which express a genetically encoded fluorescent calcium indicator in all enteric neurons and glia. Exogenous GABA increased the intracellular calcium concentration, [Ca2+]i of some myenteric neurons including many that did not express GABA or nNOS (the majority), some GABA+, Calretinin+ or Neurofilament-M (NFM)+ but rarely nNOS+ neurons. GABA+ terminals contacted a significantly larger proportion of the cell body surface area of Calretinin+ neurons than of nNOS+ neurons. Numbers of neurons with GABA-induced [Ca2+]i transients were reduced by GABAA,B,C and nicotinic receptor blockade. Electrical stimulation of interganglionic fibre tracts was used to examine possible effects of endogenous GABA release. [Ca2+]i transients evoked by single pulses were unaffected by specific antagonists for each of the 3 GABA receptor subtypes. [Ca2+]i transients evoked by 20 pulse trains were significantly amplified by GABAC receptor blockade. These data suggest that GABAA and GABAB receptors are not involved in synaptic transmission, but suggest a novel role for GABAC receptors in modulating slow synaptic transmission, as indicated by changes in [Ca2+]i transients, within the ENS.